Development of Animated Video-Based Mathematics Learning Media using Powtoons on Quadrilateral and Triangular Materials - Audy Puspa Ningrum; Nofriyandi Nofriyandi; Dedek Adrian; Indah Widiati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to determine the validity and practicality of video-based learning media development using Powtoon on square and triangular materials in the 7th grade of SM. The type of development research uses the R&D model (Research and Development) which has been modified into 7 stages, namely Potential and Problem, Data Collection, Product Design, Design Validation, Design Revision, Trial Product Testing and End Product. Research objects are video animation-based learning media using Powtoon on square and triangular materials in the 7th Grade. The test subjects are 20 students in the 8th Graduate Grade State 1 Kerinci Right. A learning media product developed using Powtoon is validated by four validators. Data validation results and practicality in the analysis by determining the average of each assessment. Results from the analysis of validation data show an average of 85.92% with criteria very valid. The elevation evaluation of the teacher's response to the use of learning media obtained an average of 85.33% with very practical criteria and the average elevation assessment of the student response of 86.48% with the criteria highly practical. Thus, it can be concluded that the learning media based on animated video using Powtoon on square and triangular material of grade VII SM tested its validity and practicality. This research needs to be continued to test its effectiveness on the cognitive abilities of students in the topics of quadrilaterals and triangles.